Values of Tolerance Through Religious Learning at Al-Hikmah Lasem Islamic Boarding School: Concepts, Strategies, and Challenges - Fatah, Ahmad; Syukur, Fatah; Ihsan, Ihsan; Saadah, Hilyatus (EDUKASIA, 2023)
This study aims to describe and analyze the internalization of tolerance values through religious learning at the Al-Hikmah Lasem Islamic Boarding School. The type of research used is field research, namely research that requires researchers to travel to the field to observe phenomena in a scientific context. The subjects in this study were Kiai, Ustaz, head of the boarding school, administrators, and students of Al-Hikmah Lasem. The criteria for students involved by researchers to determine research subjects were those who had lived in Islamic boarding schools for a range of two to four years. The results of this study revealed that the internalization of tolerance values at the Al-Hikmah Lasem Islamic boarding school was achieved through habituation strategies and exemplary strategies. The internalization process was carried out through religious learning both textually through book studies and contextually through examples and procedures for socializing and tolerance with the community. Supporting factors for achieving the internalization of the tolerance value included the motivation frequently given by caregivers, Ustaz, and administrators to the students of the Al-Hikmah Lasem Islamic Boarding School; the condition or environment of the Al-Hikmah Lasem Islamic Boarding School; the existence of supporting facilities at the Al-Hikmah Lasem Islamic Boarding School. Meanwhile, the inhibiting factors comprised the different backgrounds of students and the lack of interaction between students and the Chinatown community.